diff. eq.(adsbygoogle = window.adsbygoogle || []).push({});

--------------------------------------------------------------------------------

solve the following promblem

Y^(,,,)-3y^(,,)+31y^(,)-37y=0

i let y = e^kx

y'= ke^kx

y''=k^2e^kx

y'''=k^3e^kx

so i got this

k^3e^kx-3(k^2e^kx)+31(ke^kx)-37(e^kx)=0

e^kx(k^3-3K2+31k-37)=0

so,

(k^3-3K2+31k-37)=0

now i have to find (K)

how should i solve for (k) from this equation k^3-3K2+31k-37=0

can i use synthetic division if yes how should i use it or which other method can i use

is this right

i solve the k by synthetic division

5 1 1 -17 -65

5 30 65

1 6 13 0

so the factor is (k-5) (K^2+6k+13)

then i use this equation

(-b+-squrt(b^2-(4ac)))/2a

and got k = -3 +- 2i

and my fianl answer is

y=c1e^5x+c2e^(-3x)cos(2x)+c3e^(-3x)sin(2x)

sorry this is wrong info i type in

please dont do this problem

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Differential equation

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

Loading...

Similar Threads - Differential equation | Date |
---|---|

A Runge Kutta finite difference of differential equations | Yesterday at 6:31 PM |

I How to find a solution to this linear ODE? | Feb 21, 2018 |

A How to simplify the solution of the following linear homogeneous ODE? | Feb 18, 2018 |

A Causality in differential equations | Feb 10, 2018 |

A Numerical solution for a two dimensional 3rd order nonlinear diff. eq. | Jan 17, 2018 |

**Physics Forums - The Fusion of Science and Community**